2015
DOI: 10.1177/1066896915568991
|View full text |Cite
|
Sign up to set email alerts
|

Juxtaoral Organ of Chievitz, an Obscure Anatomical Structure Masquerading as Perineural Invasion of Mucoepidermoid Carcinoma

Abstract: The juxtaoral organ was first described by Chievitz in 1885. This is typically located deep to the medial pterygoid muscle (unilaterally or bilaterally) in the pterygomandibular space. Juxtaoral organ of Chievitz (JOOC) is usually incidentally detected in biopsies or resection specimen of other tumors but exceptionally, it can present as mass lesions. Awareness of this normal anatomic structure is important, because the epithelial islands in this area could be misinterpreted as an invasive carcinoma, mucoepide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…In our case the JOO appeared bilaterally, which agrees with what was described by Ito et al [10] and Sancheti et al [24], while the location and relations observed are consistent with what has been established in the literature [2,16,25], ruling out the possibility that it is an accessory parotid gland, as this presents a more superficial location and is relative to the parotid duct [21]. In our finding we observed a close proximity of the JOO to the roots of lower third molar, which could imply its exposure and/or damage during oral surgeries, although due to the little or no functionality that it seems to have, we consider that this damage might not be relevant to an individual's physiology.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our case the JOO appeared bilaterally, which agrees with what was described by Ito et al [10] and Sancheti et al [24], while the location and relations observed are consistent with what has been established in the literature [2,16,25], ruling out the possibility that it is an accessory parotid gland, as this presents a more superficial location and is relative to the parotid duct [21]. In our finding we observed a close proximity of the JOO to the roots of lower third molar, which could imply its exposure and/or damage during oral surgeries, although due to the little or no functionality that it seems to have, we consider that this damage might not be relevant to an individual's physiology.…”
Section: Discussionsupporting
confidence: 93%
“…Histologically the JOO is made up of nests or cords of epithelial cells that resemble a non-keratinised flat stratified epithelium with peripheral basal cells in a palisade arrangement, as well as some cylindrical cells with clear cytoplasm forming cords or glandu-lar-like tubular structures that can at times present an associated secretion product negative for mucin [24]. The epithelial cells of the JOO do not present mitotic figures and they may occasionally be associated with dystrophic calcifications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melanin pigment was present in 1 case and calcification in 2 cases. The finding of the JOOC medial to the angle of the mandible and with these histological features is further supported by four single case reports [4][5][6][7] (Table 2). Areas of degeneration resulted in microcystic changes The structure was described as a hamartoma [10] Base of tongue Biopsy of described slight abnormality 39 M Nests of bland squamoid cells close to small nerves [9] There is a single case report of the JOOC on the medial of the mandibular angle showing structures resembling Pacinian corpuscles.…”
Section: Literature Reviewsupporting
confidence: 66%